MOTIVATION OF FOSTER CHILDREN IN PARTICIPATING IN LEARNING AT LPKA KUTOARJO - Suryaningtyas, Nugraheni; Tando, Cahyoko Edi; Equatora, Muhammad Ali (Universitas Nusa Cendana, 2025)
This study aims to analyze the motivation of foster children in participating in learning at LPKA Kutoarjo. The success of schooling is significantly impacted by students' motivation to study, particularly those who are receiving coaching. Data for this study was gathered through interviews using descriptive qualitative approaches. Foster children, LPKA officers, and PKBM